(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The implementation of limited face-to-face classes is limiting students’ learning pace. YouTube has the potential to fill the gap in the classroom as an educational tool. YouTube videos integrate verbal and visual components. They provide comprehensive content; as a result, many academic skills are acquired. However, there’s a common issue of obstacles in accessing YouTube during online learning. They are unable to benefit from the educational videos on YouTube. Furthermore, the learners wanted to educate themselves voluntarily, and the references in the videos they watch on YouTube are generally for entertainment, which may cause a distraction for the learners. YouTube is a useful tool that can improve the learning experience if the video is, in fact, pertinent to the topic at hand. This study aims to know the impact of YouTube on skills acquisition on the learners and ensure the effectiveness of YouTube as an educational tool that they may use to broaden the learning environment. The study revealed that there is a problem in accessing YouTube on skills acquisition. However, despite the problems they encountered, there is still a positive impact, and learners can be responsible, committed to surviving, and flexible in this kind of learning. Researchers concluded that regardless of the problem of the learners caused by the problems encountered in Youtube, learners are still responsible in this kind of learning environment. YouTube has had a significant impact on classroom management advantages for both students and teachers. From the students’ perspectives on the usage of YouTube for learning, there are corresponding usage patterns and related factors prompting them to use YouTube. The YouTube benefits include attracting students’ attention, maintaining their focus, watching challenging occurrences, piquing their interest in the subject matter, improving content attitudes, improving content attitudes, building relationships with students, encouraging innovation, fostering teamwork, and motivating students. The researchers recommend encouraging and advising teachers to use YouTube in their own courses to take advantage of its built-in advantages in the context of learning and teaching. In accordance with the (LMS) the newest eLearning-resources that can be included in modern education teaching is YouTube.